A new Crocus L. (Iridaceae) species from SE Turkey, based on morphological and molecular data - Erol, Osman; Harpke, Doerte; Yıldırım, Hasan (Phytotaxa, 2015)
Crocus musagecitii is described as a new species. Diagnostic morphological characters, a full description and detailed illustrations are provided on the basis of the type specimen and wild specimens. Morphologically, C. musagecitii is close to Crocus biflorus subsp. pseudonubigena. Crocus musagecitii differs from C. biflorus subsp. pseudonubigena by the lack of stripes or narrow purplish tongue on outside of outer tepals, wider tepals, and homogenously yellow anthers. In order to clarify the phylogenetic position of this species within the Crocus adamii species complex, we sequenced the internal transcribed spacer region (ITS: ITS1 + 5.8SrDNA + ITS2) and 5’ external transcribed spacer (ETS) of the nuclear ribosomal DNA (rDNA). A phylogenetic tree obtained by Bayesian phylogenetic inference is given. Phylogenetic analyses revealed that the new taxon is close to C. munzurensis. Crocus musagecitii differs from its phylogenetically closest relative C. munzurensis by the corm tunics (C. musagecitii: coriaceus; C. munzurensis: membranous), the number of leaves (C. musagecitii: up to 8; C. munzurensis: up to 4) and non-hairy leaf margins.